Study on The Relationship Between Social Support and Entrepreneurship Intention Experienced by Adolescents - Rafadi Khan Khayru; Nichen Nichen; Arnadi Chairunnas; Safaruddin Safaruddin; Muhammad Tahir (Journal of Social Science Studies (JOS3), 2021)
Entrepreneurship is very important for the community because with entrepreneurship people are no longer dependent on jobs, and create job opportunities for others. Entrepreneurial activities in the community have a very important role to help overcome the problem of unemployment and increase people's income. The cause of the large number of unemployed because most people do not have an entrepreneurial spirit. The social environment has an important role in shaping the desire for entrepreneurship. The purpose of this correlational study is to determine the relationship between social support and entrepreneurial intentions. Respondents in this study were taken from the group of teenagers aged 15-20 years. The sampling technique in this study used a purposive sampling technique based on characteristics focused on groups of teenagers who had not worked and were not married. In addition, they also have no entrepreneurial experience. There are 46 teenagers who are respondents in this study. All of them came from Padusan Village, Pacet District, Mojokerto Regency. The data analysis technique used to fulfil the study objectives is product moment correlation analysis assisted by the SPSS 26 program. The research findings state that social support has a positive and significant relationship with entrepreneurial intentions. The higher the level of social support received by adolescents, the higher the level of entrepreneurial intentions possessed by adolescents